Influência do alinhamento e da placa osteoligamentar do pé na marcha de indivíduos saudáveis - Vanessa Lara de Araujo (2017)
The movements of foot pronation and supination during walking are influenced by a series of interactions that occur between tissues and joints of the lower limbs. This dissertation investigated some factors related to the lower limb distal joints that might influence foot pronation and supination during walking. The general goal of this dissertation was to investigate the influence of foot alignment and of an orthosis that simulates the foot osteoligamentous plate on lower limb biomechanics during walking. The first study investigated the effect of distinct magnitudes of foot-ankle complex varus alignment (small versus large) on kinematics and kinetics of foot, ankle, knee and hip in the frontal and transverse planes during the stance phase of walking. Twenty-eight subjects were alocated into two groups according to their footankle complex alignments in the frontal plane by means of percentile analysis: (1) values equal to or inferior to the percentile 45, and (2) values equal to or above the percentile 55. The lower limb kinematic and kinetic data was evaluated with the participant walking at self-selected speed on an instrumented treadmill. The groups with large varus alignment of the foot-ankle complex had significantly greater (p < 0.03) forefoot inversion angle at initial contact, amplitude of rearfoot-shank eversion and maximum internal moment of ankle inversion when compared to the group with small varus alignment. No significant differences (p > 0.05) between groups were found for motion amplitudes and maximum internal moments at the knee and hip. The durations of the movements of the rearfoot-shank, knee and hip were also not different between groups. The second study investigated the effect of using a foot orthosis inspired by the concept of foot osteoligamentous twisted plate on foot-ankle complex kinematics in the sagittal and frontal planes during the stance phase of walking. Thirty-five healthy participants underwent kinematic assessment of footankle complex kinematics with three different foot orthoses: (1) Spring: orthosis inspired by the concept of a twisted osteoligamentous plate shape and constructed with a stiff and elastic material (carbon fiber); (2) Flat: control orthosis made of a nonelastic material with a non-inclined surface; and (3) Rigid: control orthosis made of a non-elastic material, with the same shape of the Spring one. Spring orthosis reduced the duration and magnitude of rearfoot eversion (p 0.03), increased rearfoot inversion relative to shank (p < 0.01), increased forefoot eversion relative to rearfoot (p < 0.01), and increased the peak of plantar flexion of forefoot relative to rearfoot during the propulsive phase (p = 0.01) compared with the flat orthosis. The effects of the Spring orthosis were different from the Rigid, which demonstrated that shape was not the only determinant for the results, but also material properties. The results of this dissertation help clarifying the role of foot-ankle varus alignment and twisted foot plate mechanism on motion of foot pronation and supination during stance phase of walking.